ISOLASI DAN IDENTIFIKASI BAKTERI PENAMBAT NITROGEN UNTUK PEMBUATAN BIOFERTILIZER - asrul, asrul; Pugeg Aryantha, I Nyoman (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2021)
Nitrogen is a macro nutrient needed by plants. Generally, people use inorganic fertilizers to fulfill nitrogen nutrients in plants. The problem then is, the continuous use of synthetic nitrogen fertilizers has a direct negative impact on the soil and a derivative impact on human health. The use of microorganisms, in this case bacteria, to provide nitrogen to plants can be done by isolating it and making it a biological fertilizer agent. Nitrogen fixing bacteria was isolated on the land of the oil palm plantation of PT Astra Agro Lestari. The isolated nitrogen-fixing bacteria were then tested quantitatively for their ability to fix nitrogen. The bacteria with the highest nitrogen fixing ability were then identified by sequencing their DNA nucleotide bases so that the bacterial strains were identified. The result is that there are 13 bacteria that are able to fix nitrogen with the codes J1, J3, Q5, L1, L11, J31, D1, M6, M5, R1, P2, J4 and C7. The quantitative test shows that bacteria with code D1 are the best at fixing nitrogen in the form of NH4, namely 0.27 ppm. The results of D1 bacterial DNA nucleotide base sequencing showed that the putitive Bacillus aerius strain 24K with identical values ​​and query cover reach